2011
DOI: 10.1002/jso.21880
|View full text |Cite
|
Sign up to set email alerts
|

L1 Cell adhesion molecule (L1CAM) expression at the cancer invasive front is a novel prognostic marker of pancreatic ductal adenocarcinoma

Abstract: L1CAM could play an important role in the invasive process in vivo, and is thought to be a good indicator of prognosis in PDAC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 29 publications
2
29
2
Order By: Relevance
“…We defined the invasive front as the front edge between the tumor and the stromal tissues. When the proportion of cancer cells positive for RacGAP1 at the invasive front was C10 %, the cancer was defined as being RacGAP1-positive, and the remainder of the tumor was defined as Rac-GAP1-negative at a magnification of 2009 in reference to previous report [18]. Each sample was scored in a blinded manner by two investigators (T. S. and Y.…”
Section: Immunohistochemical Evaluationmentioning
confidence: 99%
“…We defined the invasive front as the front edge between the tumor and the stromal tissues. When the proportion of cancer cells positive for RacGAP1 at the invasive front was C10 %, the cancer was defined as being RacGAP1-positive, and the remainder of the tumor was defined as Rac-GAP1-negative at a magnification of 2009 in reference to previous report [18]. Each sample was scored in a blinded manner by two investigators (T. S. and Y.…”
Section: Immunohistochemical Evaluationmentioning
confidence: 99%
“…For several types of cancer, tumor cells at the invasive front are considered to have more aggressive behavior compared with those in the more central region [41][42][43] and are characterized by a dynamic process referred to as epithelial mesenchymal transition (EMT) [44,45]. EMT is considered to be a transient and reversible process, and represents only one of the several steps required for tumor progression via invasion and metastatic spread [46], because it has also been implicated in the fundamental steps of tumorigenesis, such as invasion and metastasis [47].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study revealed that elevated L1CAM levels were associated with shorter survival in patients with pancreatic ductal adenocarcinoma (12). In addition, studies on resected tumor samples from colorectal (32), ovarian (9), and melanoma (33) cancer patients have linked L1CAM overexpression to poor prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Deregulated expression of members of all major cell adhesion molecule families [integrins, selectins, cadherins, and the immunoglobulin (Ig) superfamily] is frequently reported in human cancers (8). One such molecule, L1 cell adhesion molecule (L1CAM), is aberrantly expressed in several cancer types, including ovarian (9), melanoma (10), breast (11), pancreatic (12), and colon cancers (13). L1CAM is a type I membrane glycoprotein of the Ig-like superfamily, consisting of 6 Ig-like domains and 5 fibronectin-type III repeats, followed by a single-pass transmembrane region and a highly conserved cytoplasmic tail (14).…”
Section: Introductionmentioning
confidence: 99%